2019
DOI: 10.24248/eahrj.v3i1.595
|View full text |Cite
|
Sign up to set email alerts
|

Family Connectedness and Its Association With Sexual Risk-Taking Among Undergraduate Students at the University of Nairobi

Abstract: Background: Universities have a student population in the age range of 17 to 25 years, 75 % of whom are sexually active, with the median age of sexual debut at age 18 years. About half of all students are involved in risky sexual behaviour. Many interventions have decreased sexual risk behaviour in the short-term, but there is need for multilevel prevention, including targeting improvements in family relationships for sustained change. Perceived positive family connectedness has been found to be related to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The enhanced family connectedness found in this study supports findings by Duggins et al (2016), who reported that family connectedness mitigates the negative effects of bullying on adolescent aggression (Duggins et al, 2016). Similarly, Wachira et al (2019) found that higher family connectedness was associated with reduced sexual risktaking behaviors among university students (Wachira et al, 2019). These studies underscore the protective role of family connectedness in various contexts, suggesting that the improvements observed in this study could have broader implications for reducing risk behaviors and enhancing psychological well-being.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The enhanced family connectedness found in this study supports findings by Duggins et al (2016), who reported that family connectedness mitigates the negative effects of bullying on adolescent aggression (Duggins et al, 2016). Similarly, Wachira et al (2019) found that higher family connectedness was associated with reduced sexual risktaking behaviors among university students (Wachira et al, 2019). These studies underscore the protective role of family connectedness in various contexts, suggesting that the improvements observed in this study could have broader implications for reducing risk behaviors and enhancing psychological well-being.…”
Section: Discussionsupporting
confidence: 85%
“…The FCS has demonstrated strong reliability, with Cronbach's alpha coefficients for the subscales and total scale exceeding 0.80 in various studies. Its validity has been confirmed through correlations with related constructs such as family functioning and emotional well-being, making it a robust tool for evaluating family connectedness in research settings (Gervais & Jose, 2019;Wachira et al, 2019;Willems et al, 2020).…”
Section: Family Connectednessmentioning
confidence: 95%
See 1 more Smart Citation
“…In our analysis, parental supervision was also a contributing factor for vulnerability in urban/peri-urban Kenya and urban Zambia. Recent research in Kenya and the region has shown that family connectedness and parental monitoring were associated with less sexual risk taking (Cluver et al 2016;Wachira et al 2019). In both Kenya and Malawi, coming from a household that did not have the poorest or the richest SES relative to the community was also a key factor in vulnerability.…”
Section: Discussionmentioning
confidence: 99%